The Ulul Albab Model by Prof. Imam Suprayogo: Merging Science, Faith, and Character in Islamic Education - Basiroh, Siti; Yusgiantara, Akbar; Baidi, Baidi (ALSYS, 2025)
This study provides a rigorous analysis of the epistemology and educational framework of Ulul Albab, a model developed by Prof. Imam Suprayogo that integrates dhikr (remembrance), fikir (critical thinking), and amal (social action) as the foundational pillars of holistic Islamic education. Positioned as a response to the persistent dichotomy between religious and secular knowledge in Islamic educational institutions, the Ulul Albab paradigm aims to foster a balanced development of intellectual, emotional, and spiritual capacities. Employing a qualitative library research design, this study critically examines Suprayogo’s original writings and compares them with other prominent Islamic scientific integration models, particularly those proposed by M. Amin Abdullah and Syed Naquib al-Attas. Findings demonstrate that the Ulul Albab model effectively embeds character education into the curriculum and equips students to navigate challenges posed by the digital age and Society 5.0 by promoting resilience, critical digital literacy, and social responsibility. However, the research also identifies implementation gaps, especially the absence of standardized methods for assessing the integration of dhikr, fikir, and amal. Conceptually, this study contributes an evaluative synthesis of Suprayogo’s approach, while practically offering recommendations for enhancing assessment tools and curriculum development in Islamic education. Future research should focus on refining evaluation frameworks and expanding the model’s application across diverse educational contexts to amplify its relevance and impact on global Islamic education.